Integrasi antara Agama dan Ilmu Dalam Perspektif Malik Bennabi - Sujiat Zubaidi; M. Kharis Majid; Abdullah Muslich Rizal Maulana (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
As a Muslim sociologist, Malik Bennabi has both an answer and a criticism of western scholars' opinions on the dichotomy between science and religion. In this paper, the author tries to describe and analyze malik Bennabi's pattern of thinking related to the integration between religion and science. In this brief study, it can be seen that according to Bennabi between science and religion has a very close relationship, even the two have a single role in the formation of a civilization. This is certainly what is meant by Islamic civilization. Islamic civilization is a civilization of science, even Islam itself is a religion and civilization, so in Islamic civilization between science and religion is an inseparable unity. While Western civilization according to Bennabi at this time is on the verge of destruction, because of the moral decadence manifested from the dichotomy between religion and Science. This is because basically the identity of Western civilization itself must be a separation between science and religion, namely with secularization. Gradually but surely European culture has melted away with secular travel, which further led them towards positivism and materialism. From there science and morals have their own paths, so the separation between science and conscience becomes common in areas covered by secular culture.